LITIGASI SENGKETA EKONOMI SYARIAH: STRATEGI DAN PRAKTIK ADVOKAT FIRMA HUKUM KARIMATA - Dela Puspita Sari; Sofiatus Sobriyah; Siti Rohmah; Siti Aisyah (ESA, 2026)
The development of the Sharia-based financial and business industry in Indonesia has driven an increase in economic transactions using Sharia contracts. On the other hand, this dynamic has also given rise to various disputes related to breach of contract, contract enforcement, and differences in interpretation of Sharia contracts. In certain circumstances, these disputes cannot be resolved through non-litigation channels and must be pursued through litigation in the courts. Therefore, the role of advocates is crucial in formulating litigation strategies that are not only based on positive law but also consider the principles of Sharia economics. This study aims to analyze the strategies and practices of advocates in handling Sharia economic dispute litigation, specifically the advocacy practices carried out by advocates at the Karimata Law Firm. This study uses a qualitative approach with a case study design. Data were obtained through in-depth interviews with advocates experienced in handling Sharia economic cases, observations of advocates' work processes in handling cases, and documentation and literature review related to Sharia economic law and litigation practices. The collected data was then analyzed qualitatively through data reduction, data presentation, and conclusion drawing to gain a comprehensive understanding of advocacy strategies for resolving Sharia economic disputes through litigation. The research findings indicate that the practice of Sharia economic dispute litigation has unique characteristics that require advocates to integrate an understanding of positive law with Sharia economic principles. An effective litigation strategy begins with an in-depth case analysis, including examining contract documents, identifying potential breaches of contract, and mapping the parties' legal positions. Furthermore, the success of a case is greatly influenced by the advocate's ability to develop systematic and evidence-based legal arguments. The research findings also indicate that an advocate's practical experience plays a crucial role in understanding trial dynamics and formulating appropriate strategies during the litigation process. Furthermore, good communication between the advocate and the client is a supporting factor in maintaining information consistency and strengthening the legal position in court. Therefore, the success of Sharia economic dispute litigation is determined not only by the normative aspects of the law but also by the advocate's professional competence in managing a structured advocacy strategy aligned with the values ​​of justice in Sharia principles.